Building Psychological Resilience in Maritime Cadets: A Mixed-Methods Investigation of Stressors, Protective Factors, and Support Interventions in Indonesian Maritime Education (International Journal of Economics Management and Social Science, 2026)
Maritime cadet training involves significant psychological demands that contribute to burnout, attrition, and mental health challenges, yet maritime education institutions rarely address resilience systematically. This mixed-methods study examined psychological stress factors, resilience-building mechanisms, and effectiveness of peer mentoring and digital wellness interventions among 287 maritime cadets from STIP Jakarta and affiliated maritime schools. Qualitative interviews with 42 cadets, educators, and mental health professionals identified primary stressors: academic performance anxiety, homesickness, separation from families due to practical sea training, insufficient sleep, and concern about employment prospects. Resilience factors included peer support networks, meaningful instructor relationships, clear career pathways, and institutional recognition of psychological wellbeing. Quantitative survey analysis (Cronbach's α = 0.82) revealed that cadets with structured peer mentoring reported 34% lower stress symptoms and 28% higher psychological well-being compared to peers without mentoring support. A pilot digital wellness platform with mobile notifications for mindfulness exercises, emotional check-ins, and peer connection features demonstrated feasibility and user acceptance (mean satisfaction rating 4.2/5.0). The integrated support model combining peer mentoring, instructor recognition of mental health dimensions, curricular resilience-building activities, and accessible digital wellness resources produced measurable improvements in cadet psychological wellbeing while maintaining academic rigor. Findings demonstrate that maritime institutions can integrate mental health support into professional training without compromising maritime safety standards or operational competency development. Keywords :  Maritime cadets; Psychological resilience; Mental well-being; Peer mentoring; Stress management; Maritime education; Wellness interventions